1984
DOI: 10.3354/meps020185
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in the macrofaunal associates of pelagic Sargassum and some biogeographic implications

Abstract: The macrofauna associated with individually collected clumps of pelagic Sargassurn was influenced strongly by the location of sampling. Algae collected in the Sargasso Sea carried more species with lower dominance and higher evenness and variation in abundance than algae collected in the Gulf Stream. Gulf Stream samples were dominated by the shrimp Latreutes fucorum (67.8 %) with little compositional variation whereas the gastropod Litiopa melanostoma was the most abundant but weakly dominant species (25.1 %) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
57
4

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 15 publications
8
57
4
Order By: Relevance
“…Results showed that the more densely branched mimic "complex alga" had a greater number of amphipods, which also showed a dependence on both size-specific selections for the structural and spatial components of habitat architecture. These results have also been reported in other studies (Heck and Wetstone, 1977;Crowder and Cooper, 1982;Coull and Wells, 1983;Edgar, 1983aEdgar, , 1983bEdgar, , 1983dStoner and Lewis, 1985;Dean and Connell, 1987a, 1987b, 1987cHacker and Steneck, 1990). Habitat architecture should be explored not only horizontally (i.e., patch size or how densely packed the alga is arranged), but also vertically (the depth the alga covers in the water column).…”
Section: Introductionsupporting
confidence: 50%
“…Results showed that the more densely branched mimic "complex alga" had a greater number of amphipods, which also showed a dependence on both size-specific selections for the structural and spatial components of habitat architecture. These results have also been reported in other studies (Heck and Wetstone, 1977;Crowder and Cooper, 1982;Coull and Wells, 1983;Edgar, 1983aEdgar, , 1983bEdgar, , 1983dStoner and Lewis, 1985;Dean and Connell, 1987a, 1987b, 1987cHacker and Steneck, 1990). Habitat architecture should be explored not only horizontally (i.e., patch size or how densely packed the alga is arranged), but also vertically (the depth the alga covers in the water column).…”
Section: Introductionsupporting
confidence: 50%
“…Many authors have reported on the temporal and geographical variation of the mobile fauna (Timmermann, 1932;Fine, 1970;Butler et al, 1983;Stoner & Greening, 1984) but regarding the sessile fauna and flora mainly qualitative descriptions are available (Hentschel, 1922;Prat, 1935;Burkenroad, 1939;Weis, 1968;Morris & Mogelberg, 1973;Woelkerling, 1975;Butler et al, 1983). Quantitative analyses have been carried out in relation to settlement and succession of epibionts by Conover & Sieburth (1964) and Ryland (1974).…”
Section: Introductionmentioning
confidence: 99%
“…The composition of rafting communities on macroalgae collected from the sea surface after extended floating periods has been studied by Stoner & Greening (1984), Hobday (2000) and Tsikhon-Lukanina et al (2001). Similarly, experimental investigations have focused on later successional stages of the rafting community on detached and tethered macroalgae that had been suspended in the water column or at the sea surface for weeks to months (Edgar, 1987;Vásquez, 1993;Ingólfsson, 1998).…”
Section: Introductionmentioning
confidence: 99%